Predictors of Response to Therapy among Post Thyroidectomy Adult Filipino Patients with Papillary Thyroid Carcinoma based on the 2015 American Thyroid Association Guidelines - Santiago, Aivind Gabrielle; Isidro, Maria Jocelyn; Parra, Joseph (Journal of the ASEAN Federation of Endocrine Societies, 2022)
<center> </center><center> </center> *Visual Abstracts prepared by Dr. Carmen Carina Cabrera Objective. To identify factors independently associated with incomplete response to therapy based on the 2015 ATA guidelines in surgically treated Filipino patients with papillary thyroid carcinoma (PTC). Methodology. This is a retrospective cohort study of adults aged 21-74 years with papillary thyroid carcinoma (PTC) treated with surgery with or without radioactive iodine therapy (RAI) in Makati Medical Center from 2013 to 2017. We collected the following factors through a review of charts: age at diagnosis, gender, family history of thyroid cancer, date of surgery, tumor size, capsular/lymphovascular invasion, lymph node/distant metastases, stage, risk of recurrence, dose of post-surgical RAI therapy, initial post-treatment serum Thyroglobulin (Tg) and anti-Tg antibody levels (Negative Tg level: suppressed non-stimulated Tg <0.2 ng/mL or TSH-stimulated Tg <1 ng/mL; Positive Tg level: suppressed Tg >1 ng/mL or a TSH-stimulated Tg >10 ng/mL or rising anti-Tg antibody levels), thyroid stimulating hormone suppression, post-operative imaging studies and levothyroxine dose. Response to therapy was checked 6-24 months post-therapy. Results. We analyzed a total of 115 patients with PTC who underwent thyroidectomy. Patients who had family history of thyroid cancer were less likely to have an incomplete or indeterminate response (p=0.045). None of the patients with excellent response had lymphovascular invasion. Having a positive Tg (p=0.001) and positive anti-Tg postoperatively (p<0.001) were strongly associated with incomplete or indeterminate response. Conclusion. Patients who were positive for thyroglobulin and anti-thyroglobulin post-operatively were strongly associated with incomplete or indeterminate response to therapy in PTC.